Geotechnical issues of shallow mining within the Upper Silesian Industrial Region - Labus, Krzysztof (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Mining activity, within the Upper Silesian Industrial Region resulted in numerous mining damage - especially the discontinuous deformations. They are developed in effect of shallow coal seams extraction or are connected with Zn-Pb ore mining. Within the Syncline of Bytom the shallow ore mining, folIowed by coal mining, carried out at bigger depth led to reactivation of abandoned ore workings, and formation of mining damage to the surface.
Keywords: geotechnika; górnictwo; Górnośląski Okręg Przemysłowy; geotechnics; mining; Upper Silesian Industrial Region